Pembelajaran Fikih Berbasis ASSURE Model - Mukarromah; Putri, Sabrina Aisyah (Pelita: Jurnal Studi Islam Mahasiswa UII Dalwa, 2023)
In the 21st century learning environment which is closely linked to the use of digital tools, educators need to plan new things to create a learning atmosphere that suits the character of students. The research methodology used in this writing is a qualitative approach with the type of research in the form of a literature review. ASSURE learning model is an abbreviation for Analyze learner characteristics, State performance objective, Select (methods, media and materials), Utilize materials, Require learner participation, Evaluation and revise. Namely the process of designing a learning model from analyzing student character, learning methods, selecting and applying appropriate learning methods and media and carrying out evaluations and revisions during learning. Developing Islamic Religious Education learning media through ASSURE Model appropriately will provide benefits for teachers and students in making learning effective.